Secular Trends of Physical Fitness in Twenty-Five Birth Cohorts of Slovenian Children: A Population-Based Study - Potočnik, Žan Luca; Jurak, Gregor; Starc, Gregor (Frontiers in Public Health, 2020)
In Slovenia, the national SLOfit surveillance system of the somatic and motor development of children and youth has been enabling researchers to observe the developmental trends of the entire population of school-aged children since 1987. The national database currently incorporates over 7.2 million sets of measurements of eight fitness tests and three anthropometric measurements. Since 1991, as in the rest of the world, in Slovenia, there is a common perception that the physical fitness of contemporary children is in decline and below the level of the physical fitness of the previous generation's childhood fitness. Our paper examines the trends of physical fitness in 26 birth cohorts of 7–10-year-olds. The analysis shows that the secular trends of physical fitness in boys and especially in girls have been positive and that the level of physical fitness of recent birth cohorts exceeds the national average of physical fitness of the 1989–2019 period. At the same time, the analysis reveals that the distribution of physical fitness has been changing from almost normal in the cohorts born in the first half of the 1980s, toward positively skewed in the subsequent cohorts born before the year 2000, and bimodal distribution in the later cohorts, indicating growing inequality and polarization of the motor development of children.